Osteosarcoma immune prognostic index can indicate the nature of indeterminate pulmonary nodules and predict the metachronous metastasis in osteosarcoma patients - He, Xuanhong; Lu, Minxun; Hu, Xin; Li, Longqing; Zou, Chang; Luo, Yi; Zhou, Yong; Min, Li; Tu, Chongqi (Frontiers in Oncology, 2022)
Purpose: The relationship between indeterminate pulmonary nodules (IPNs ) and metastasis is difficult to determine. We expect to explore a predictive model that can assist in indicating the nature of IPNs, as well as predicting the probability of metachronous metastasis in osteosarcoma patients. Patients and methods: We conducted a retrospective study including 184 osteosarcoma patients at West China Hospital from January 2016 to January 2021. Hematological markers and clinical features of osteosarcoma patients were collected and analyzed. Results: In this study, we constructed an osteosarcoma immune prognostic index (OIPI) based on lung immune prognostic index (LIPI). Compared to other hematological markers and clinical features, OIPI had a better ability to predict metastasis. OIPI divided 184 patients into 4 groups, with the none OIPI group (34 patients), the light OIPI group (35 patients), the moderate OIPI group (75 patients), and the severe OIPI group (40 patients) (P<0.0001). Subgroup analysis showed that the OIPI could have a stable predictive effect in both the no-nodule group and the IPNs group. Spearman's rank correlation test and Kruskal–Wallis test demonstrated that OIPI was related to metastatic site and metastatic time, respectively. In addition, patients with IPNs in high OIPI (moderate and severe) groups were more likely to develop metastasis than those in low OIPI (none and light) groups. Furthermore, the combination of OIPI with IPNs can more accurately identify patients with metastasis, in which high OIPI group had a higher metastasis rate, and severe OIPI group tended to develop metastasis earlier than none OIPI group. Finally, we constructed an OIPI-based nomogram to predict 3- and 5-years metastasis rates. This nomogram could bring net benefits for more patients according to the decision curve analysis and clinical impact curve. Conclusion: This study is the first to assist chest CT in diagnosing the nature of IPNs in osteosarcoma based on hematological markers. Our findings suggested that the OIPI was superior to other hematological markers, and that OIPI can act as an auxiliary tool to determine the malignant transformation tendency of IPNs. The combination of OIPI with IPNs can further improve the metastatic predictive ability in osteosarcoma patients.